Intraprostatic Hydatid Cyst: An Unusual Presentation - Yassine Nouira; Mohamed Y. Binous; Kais Nouira; Amina Mekni; Yousri Kallel; Zouhaier Fitouri; Sataa Sallami; Ali Horchani (The Scientific World Journal)
A case of intraprostatic cyst is reported. The patient presented with a completely evacuated hydatid cyst of the prostate. The intraprostatic cystic cavity that was communicating with the urethra developed urinary stones. The patient had transurethral resection of the prostate, the stones in the cyst were pushed into the bladder and fragmented using a ballistic lithotripter. Pathological examination concluded to a prostatic hydatid cyst that had evacuated through the urethra and was complicated by stone formation within the residual cavity. Postoperative course was uneventful and follow-up did not show evidence of recurrence. This is the first case of hydatid cyst of the prostate to present as an intraprostatic stone pouch.